Kewirausahaan JASA LAYANAN SURVEY PEMETAAN SEBAGAI IMPLEMENTASI KESIAPAN BERWIRAUSAHA SISWA SMK - RIKA AYU WIBOWO (Jurnal Qua Teknika, 2024)
Various competences have been given to the students of the Vocational School (SMK), in particular the specialization program of Teknik Konstruksi dan Perumahan. One such competence is to be able to understand the types of measuring instruments, the operation and maintenance of simple and professional measurement instruments (manual and digital), as well as the data of measurements, and to be capable of understanding the business processes of construction and housing work, including the planning and implementation of housing construction. The growing market demand for surveys and mapping, as well as extensive business opportunities, gave rise to the idea of familiarizing students with entrepreneurship. In addition to meeting the needs of the industry, this idea aims to prepare students to enter the world of entrepreneurship. SME graduates are expected to be able to create jobs for themselves and others. With this idea and supported by existing curricula, SMK students should get used to having an entrepreneurial spirit. The purposes and implementation of the curriculum can be achieved through survey and mapping services, with the hope that students can design and implement an entrepreneurship program in the form of Mapping Survey Services as Implementation of Entrepreneurial Preparedness, Students of SMK Negeri 2 Surabaya.